Understanding the potential for tsunami generated by earthquakes on the southern Hikurangi subduction interface. Issue 1 (2nd January 2016) - Power, W; Wallace, LM; Mueller, C; Henrys, S; Clark, K; Fry, B; Wang, X; Williams, C
ABSTRACT: The earthquake and tsunami potential of the southern Hikurangi subduction interface has been assessed by reviewing current research in paleoseismology, paleotsunami, geodesy and passive and active source seismology. In addition, new interpretations of seismic lines are presented demonstrating the location and influence of splay faults and a modelling study examines the sensitivity of tsunami in Cook Strait to the southern termination of Hikurangi earthquake ruptures. Key conclusions are: the southern portion of the Hikurangi interface, south of c. 40°S, is currently strongly coupled and experiences great megathrust earthquakes of M w >8 (some of which may also rupture further north); the downdip limits of strong coupling at southern Hikurangi are outlined by slow slip events and non-volcanic tremor; and the behaviour at the updip limit and the southern termination will be strongly influenced by splay faults. The tsunami impact on Cook Strait is shown to be highly sensitive to how far ruptures extend across Cook Strait.